(untitled) (Analysis in Theory and Applications, 2018)
Let A:=−( abla−ia)·( abla−ia)+V be a magnetic Schrödinger operator on L^2(R^n), n≥ 2, where a := (a_1 ,···,a_n) L^2_loc(R^n, R^n) and 0≤ V L^1_loc(R^n). In this paper, we show that for a function b in Lipschitz space Lip_α (R^n) with α(0,1), the commutator [b, V^1/2A^-1/2] is bounded from L^p(R^n) to L^q(R^n), where p, q(1,2] and 1/p−1/q = α/n.